PELATIHAN KEWIRAUSAHAAN MELALUI DIVERSIFIKASI SAYUR MAYUR BERUPA ICE CREAM BAGI WARGA DESA DUWET KEC. TUMPANG KAB.MALANG - Ellyn Eka Wahyu; Yekie Senja Oktora (P3M Politeknik Negeri Malang, 2024)
The agricultural and plantation potential produced by Duwet Village includes vegetables. Several types of vegetables produced include mustard greens and tomatoes. These two types of vegetables have great potential to develop their production, not only as complementary vegetables to food dishes consumed daily by families; However, it can be developed into a food product that is more varied and has more selling value, is popular, attractive but still healthy. The problem is that mustard greens and tomatoes still receive very little processing attention so that their selling value can be increased. The existing mustard greens and tomatoes are generally only for sale and/or processed for daily food needs without any other processing alternatives due to the limited knowledge of residents to manage these mustard greens and tomatoes so that they become a product that has product value and selling value. higher. This PPM activity seeks to provide understanding through entrepreneurship training by diversifying mustard greens and tomatoes into ice cream. From this Community Service (PPM) activity, it is hoped that synergy will be created between the residents of Duwet Village, Kec. Overlapping District. Malang with the Malang State Polytechnic, to be able to help partners increase their knowledge so they can produce/process mustard greens and tomatoes as one of the superior products and sell products with a higher selling value and can help the local economy continuously.